Effectiveness of low-level laser therapy on recovery from neurosensory disturbance after sagittal split ramus osteotomy: a systematic review and meta-analysis - Parsa Firoozi; Seied Omid Keyhan; Seong-Gon Kim; Hamid Reza Fallahi (SpringerOpen, 2020)
Abstract Background Orthognathic surgery such as bilateral sagittal split ramus osteotomy (BSSRO) for the treatment of mandibular deformities is one of the most common procedures in maxillofacial operations that may lead to neurosensory disturbance. In this study, we aimed to evaluate the effectiveness of low-level laser therapy (LLLT) on augmenting recovery of neurosensory disturbance of inferior alveolar nerve (IAN) in patients who underwent BSSRO surgery. Methods A comprehensive literature search was conducted by two independent authors in PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), Scopus, Embase, and Google Scholar electronic databases. Besides, a manual search of all textbooks and relevant articles were conducted. Searches took place in August 2020 and were limited to published and peer-reviewed articles from 2000 to 2020. All analysis was performed using the comprehensive meta-analysis (CMA) and the STATA MP (version:16) software. The weighted mean difference (WMD) using the inverse variance method and the standard mean difference (SMD) was considered for continuous variables. Results Seventy-four papers were retrieved after removing duplicate studies and finally, eight studies were assessed for qualitative synthesis and five for meta-analysis. Totally, 94 patients were included in the meta-analysis. Based on the meta-analysis, it was shown that LLLT was not effective in a short interval (0 to 48 h) after surgery, but in a period of more than 1 month after surgery, the positive results of treatment can be observed strikingly. Also, LLLT side/group showed no significant difference in some aspects of neurosensory recovery such as thermal sensation compared to the placebo side/group. Conclusions The meta-analysis of randomized controlled trials revealed that LLLT generally improves IAN sensory disturbance caused by BSSRO. Further high-quality clinical trials with longer follow-up periods and larger sample sizes are recommended.